Teaching resource for the acquisition of cognitive skills in nursing applied to technologies - Higuera-RodrígueZ, Ana Loreta (2024)
In the process of preparation of the subject Nursing applied to technologies, the teaching staff realized that the recommended basic bibliography is very extensive and scattered, an updated compilation of theoretical and practical contents that address the topics of the subject is made. The purpose of the work is to elaborate a teaching resource, which provides students with theoretical-practical knowledge for the subject Nursing Applied to Technologies. Theoretical level methods are used: analytical-synthetic and inductive-deductive, empirical level: observation, surveys, review of documents and mathematical statistical methods: percentage analysis. The main results show that the teachers who are part of the subject group express the difficulty that students have to perform independent studies and extra-class work; in addition to consulting various bibliographies, they search the Internet in non-certified sites, obtaining information that is not in accordance with the objectives to be achieved, also surveys are applied to students who received the subject, to know their main concerns related to the bibliography they had, from the information obtained, the teaching resource is elaborated. It concludes that there are difficulties in the use of the bibliography oriented to the subject, so it is necessary to elaborate a teaching resource "Nursing from a Technological point of view" that contributes to the achievement of the proposed objectives.